2023
DOI: 10.1039/d3ce00607g
|View full text |Cite
|
Sign up to set email alerts
|

Linker length-dependent hydrogen peroxide photosynthesis performance over crystalline covalent organic frameworks

Abstract: Molecular engineering-tuned covalent organic frameworks (COFs) have demonstrated as the promising photocatalysts for photocatalytic hydrogen peroxide (H2O2) production by two-electron oxygen reduction in water. Herein a simple strategy by altering...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Three imine-based linkers (4,4''-p-terphenyldiamine (DTP), 4,4'-biphenyldiamine (BD), and 1,4-benzenediamine (PA)) production rate observed in the longer linker. [52] Such performance was ascribed to the more efficient e À /h + dissociation and higher surface area in the longer linker. Very recently, Thomas's group also reported two kinds of quinoline-linked COFs (DMCR-1NH and PMCR-1), exhibiting excellent chemical stability and photostability than imine-lined COFs.…”
Section: Functional Groups Modificationmentioning
confidence: 99%
“…Three imine-based linkers (4,4''-p-terphenyldiamine (DTP), 4,4'-biphenyldiamine (BD), and 1,4-benzenediamine (PA)) production rate observed in the longer linker. [52] Such performance was ascribed to the more efficient e À /h + dissociation and higher surface area in the longer linker. Very recently, Thomas's group also reported two kinds of quinoline-linked COFs (DMCR-1NH and PMCR-1), exhibiting excellent chemical stability and photostability than imine-lined COFs.…”
Section: Functional Groups Modificationmentioning
confidence: 99%
“…Kong and co-workers also showed that the photocatalytic activity for H 2 O 2 generation can be regulated by changing the length of the linkers used in the construction of the imine-based COFs with similar alkynyl and phenolic groups. 112 respectively (Figure 14a). Among them, COF-BPDA-DTP with the longest linker showed a higher H 2 O 2 generation rate of 1164 μmol h −1 g −1 with better stability in O 2 -presaturated water (Figure 14c).…”
Section: ■ Effect Of Different Functional Groupsmentioning
confidence: 98%
“…(c) Time course photocatalytic H 2 O 2 generation (5 mg of the catalyst, λ > 420 nm, 40 mL of deionized water). Reproduced with permission from ref . Copyright 2023, Royal Society of Chemistry.…”
Section: Effect Of Different Functional Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the obtained COF with a longer linker (COF-BPDA-DTP) exhibited better photocatalytic performance due to its more negative conductor band, higher specific surface area and enhanced photogenerated carrier separation efficiency. 43 To systematically examine the effects of different functional groups on the photocatalytic performance of a specific COF, Wang and co-workers synthesized a series of imine-linked COFs (TAPB-PDA-X) by the condensation of 1,3,5-tris(4-aminophenyl) benzene (TAPB) and the teraphthaldehyde with different functional groups (PDA-X, X = H 2 , CH 3 , OH, and OCH 3 ). Among all the obtained COFs, the TAPB-PDA-OH modified with hydroxyl groups exhibited the best H 2 O 2 production rate of 2117.6 μmol g −1 h −1 and an AQY of 2.99% at 420 nm in H 2 O : EtOH (9 : 1) aqueous solution.…”
Section: Strategies To Realize Improved Photocatalytic H2o2 Evolution...mentioning
confidence: 99%